Factors that influence fast food consumption behavior among hospitality students at Universiti Utara Malaysia Sintok, Kedah / Nur Syahirah Sahak & Nur Afif Nabilah Abu Bakar - Sahak, Nur Syahirah; Abu Bakar, Afif Nabilah (Faculty of Hotel and Tourism, 2018)
Fast food restaurant becomes wisely adopted in developing country including Malaysia. This is because the demand for fast food is increasing among Malaysian citizen that prefer eaten away from home. Fast food is a type of food that able to be prepared in a short time period and sell to the customer at a reasonable price. Therefore, this research is conducted to study the factors that influence fast food consumption behavior among Hospitality students at Universiti Utara Malaysia (UUM), Sintok, Kedah. Conceptually, the independent variable (trust, health awareness, availability and subjective norms) will be affected by the dependent variables (fast food consumption behavior). By using descriptive research design for this study, the researcher would have a deeper understanding of factors that influence university students to consume fast food at fast food restaurant in Malaysia. The survey has been conducted by distributing a questionnaire to the sample size of the population which is the students who majoring Hospitality courses at UUM. Then, the data and information collected were analyzed by using Software Package for Social Sciences (SPSS). The result shows that the factors of trust, availability and subjective norms can influence fast food consumption behavior. Besides, the most critical factor that influence fast food consumption behavior in this study is subjective norms.